Strengthening Healthcare Supply Chains: A Comprehensive Strategy for Resilience in the Face of Natural Disasters - Mimi Lima (Health Economics and Management Review)
Effective and uninterrupted management of the healthcare supply chain and healthcare system preparedness for natural disasters (e.g., pandemics, earthquakes, forest fires, etc.) is essential to ensure that victims receive critical healthcare services and products with minimal disruption, even in the event of damage to transport and logistics infrastructure as a result of significant disasters. The article examines this issue using the example of Vital Health Systems, a prominent hospital system with multiple facilities across a wide region. The qualitative data for the study was collected through interviews and focus groups with key stakeholders in Vital Health Systems, including supply chain managers, procurement specialists, frontline staff, etc. The quantitative data for the study were based on reports, internal documentation and archival documents, industry reports, market research, government databases. Analysis of the supply chain resilience of Vital Health Systems to natural disasters was carried out using the PESTLE framework, based on which a comprehensive risk reduction strategy was proposed. This strategy, while rooted in theory, is highly practical and feasible, with measures to optimise stocks, creation of alternative transport routes and logistics networks, and use of technological solutions. Organisational and managerial proposals for minimising supply chain disruptions for Vital Health Systems in the event of natural disasters are based on the theory of transformational leadership, Denison’s organisational culture, Levitt’s diamond model, and McKinsey’s theory of strategic horizons. The role of healthcare professionals, supply chain managers, procurement specialists, and researchers in healthcare management and disaster preparedness is crucial in implementing these strategies.